Answer:
Hi there!
The answer to this question is: 6x+3
Step-by-step explanation:
Step 1: combine alike terms
in the equation there are two numbers that end with x: 8x and -2x
you simply add them together to get 6x
Step 2: combine numbers
in this equations there are two numbers: 7 and -4
you simply add them together to get 3
Then your final answer should be 6x+3
That person is getting $14.50 more. Since he gets a 5% increase from the set $290, you must multiply .05 (the percentage) with 290 (that person's original load payment). When you do so, you get $14.50 and that would be how much more the person is getting paid.
Answer:
e = 29.0 will be the answer.
Step-by-step explanation:
Use the sine rule in the given triangle,
![\frac{EF}{\text{sin}(\angle D)}=\frac{DE}{\text{sin}(\angle F)}=\frac{DF}{\text{sin}(\angle E)}](https://tex.z-dn.net/?f=%5Cfrac%7BEF%7D%7B%5Ctext%7Bsin%7D%28%5Cangle%20D%29%7D%3D%5Cfrac%7BDE%7D%7B%5Ctext%7Bsin%7D%28%5Cangle%20F%29%7D%3D%5Cfrac%7BDF%7D%7B%5Ctext%7Bsin%7D%28%5Cangle%20E%29%7D)
![\frac{d}{\text{sin}(35)}=\frac{16}{\text{sin}(30)}=\frac{e}{\text{sin}(115)}](https://tex.z-dn.net/?f=%5Cfrac%7Bd%7D%7B%5Ctext%7Bsin%7D%2835%29%7D%3D%5Cfrac%7B16%7D%7B%5Ctext%7Bsin%7D%2830%29%7D%3D%5Cfrac%7Be%7D%7B%5Ctext%7Bsin%7D%28115%29%7D)
![d=\frac{16\times \text{sin}(35)}{\text{sin}(30)}](https://tex.z-dn.net/?f=d%3D%5Cfrac%7B16%5Ctimes%20%5Ctext%7Bsin%7D%2835%29%7D%7B%5Ctext%7Bsin%7D%2830%29%7D)
d = 18.35
![\frac{16}{\text{sin}(30)}=\frac{e}{\text{sin}(115)}](https://tex.z-dn.net/?f=%5Cfrac%7B16%7D%7B%5Ctext%7Bsin%7D%2830%29%7D%3D%5Cfrac%7Be%7D%7B%5Ctext%7Bsin%7D%28115%29%7D)
![e=\frac{16\times \text{sin}(115)}{\text{sin}(30)}](https://tex.z-dn.net/?f=e%3D%5Cfrac%7B16%5Ctimes%20%5Ctext%7Bsin%7D%28115%29%7D%7B%5Ctext%7Bsin%7D%2830%29%7D)
e = 29.002
e ≈ 29.0
Therefore, e = 29.0 will be the answer.
Answer:
f^(-1)(x) = \frac{-1}{5} (x+4)
Step-by-step explanation:
Given is a function
![f(x) = -5x-4\\](https://tex.z-dn.net/?f=f%28x%29%20%3D%20-5x-4%5C%5C)
To find its inverse.
We must check whether f is one to one or onto first
If -5x1-4 = -5x2-4 we get x1=x2
Hence f is one to one
Also for every f(x) we can find a x so f is onto.
So inverse exists
Let
![y=-5x-4\\-5x=y+4\\x=\frac{-1}{5} (y+4)](https://tex.z-dn.net/?f=y%3D-5x-4%5C%5C-5x%3Dy%2B4%5C%5Cx%3D%5Cfrac%7B-1%7D%7B5%7D%20%28y%2B4%29)
Replace x by f inverse and y by x
![f^(-1)(x) = \frac{-1}{5} (x+4)](https://tex.z-dn.net/?f=f%5E%28-1%29%28x%29%20%3D%20%5Cfrac%7B-1%7D%7B5%7D%20%28x%2B4%29)